Temporal interaction information and laser evoked responses: preliminary results in fibromyalgia patients with small fibers pathology - Clemente, Livio; La Rocca, Marianna; Stramaglia, Sebastiano; Marinazzo, Daniele; Lombardi, Raffaella; Lauria, Giuseppe; de Tommaso, Marina (Frontiers in Network Physiology, 2025)
ObjectivesWe propose a novel application of higher-order information-theoretic measures to assess the temporal interaction information (TII) between laser-evoked potentials (LEPs) and individual pain ratings in healthy subjects and patients with fibromyalgia (FM) affected by small fiber pathology.MethodsSeventy-nine FM patients, categorized into three groups based on skin biopsy findings (normal innervation n 19, proximal denervation n 53, and both proximal and distal denervation n 7), and 14 control subjects were studied. We used cluster-based permutation tests (p < 0.05) to identify significant clusters of TII between cortical components recorded using a 64-channel electroencephalography (EEG) system - with focus on the Cz electrode - and subjective pain ratings to quantify synergy or redundancy between the LEP signal time points and Visual Analog Scale (VAS).ResultsControl subjects generally exhibited synergy clusters corresponding to N2 and P2 peaks, whereas patients with fibromyalgia (FM), particularly those with distal denervation, exhibited increased redundancy and decreased synergy.ConclusionPatients with FM and small fiber pathology exhibited an alteration in higher-order integration mechanisms due to a complex interaction between cortical processing of pain and denervation of nociceptive fibers.SignificanceThese findings highlight the potential of TII in elucidating the complex interplay between peripheral nerve integrity and central sensitization in FM and other chronic pain disorders.